Growth of precursor stabilized IZO thin films and study of their optical and photoluminescence properties. (2022) - Ganesh, V.N.; Sanil, Chaithra M.; Jayarama, A.; Bhat, Shashidhara; Rai, C. Shantharama; Pinto, Richard
Abstract: ZnO thin films doped with Indium were produced on glass substrates by the process of spray pyrolysis. XRD results showed a polycrystalline hexagonal wurtzite structure. The structural, PL and optical characteristics of IZO thin films were investigated with increasing doping concentration. X ray diffraction studies with increasing Indium doping concentration show a change in the preferential orientation from 0 0 2 to 1 0 1 crystal planes. UV–vis-NIR spetra was collected and the results show that the band gap of the IZO thin film was found to be 3.5 eV. The optical transmittance spectra for thin films coated with 3 at% Indium concentration revealed high transmittance of 80–90% in the visible region. Other than the characteristic blue-green emission in In-doped thin films three more PL emissions were observed.